Designing Information Systems for General Administration Management in Playgroups in North Cimahi District - M Fitriawati; R H Lestari (International Journal of Research and Applied Technology (INJURATECH), 2022)
The process of implementing early childhood education at the playgroup level in its management includes program planning, organizing, implementing work plans, and monitoring. This research will discuss about management at the level of the playgroup which concerns general administration management. Where this general administration management contains important documents regarding the implementation of playgroups which are still being done manually on physical documents that may be damaged, so that important data in these documents experiences the same thing. Therefore, an information system design is needed to overcome these problems. This design uses the prototype method as a method of developing information systems. The results of this design will be used by programmers as material for making information systems